Developing Digital Government in Some Asian Countries and Lessons for Vietnam - Thi Cam Thanh, Vu (VNU Journal of Science: Policy and Management Studies, 2022)
As the technological revolution is changing the world quickly, new technologies applied in industries and fields have brought breakthroughs in every espect of economy and society. Understanding the inevitability of digital transformation and the importance of digital government, most countries in the world, including Vietnam, have been putting efforts into making policies and strategies for developing digital government. This research will focus to define the concepts and characteristics of digital transformation and digital government; to analyse the experience of developing digital government of some typical Asian countries such as Singapore, Thailand and Korea; thereby, to find out lessons for Vietnam in the process of digital transformation of government activities. Keywords: digital government, international experience, digital transformation.